Perception Student to Use Games Education as A Learning Medium Interactive at MA Tuhfatul Ulum - Qudsiyatul Hasanah; Dyan Yuliana; Arico Ayani Suparto (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Perception become indicator important in evaluate success something innovation especially in the field of education. Through perception, a teacher can understand How a learning medium accepted and felt by participants educate. Educational games No only viewed as activity play solely, will but also can utilized as a learning medium that supports the understanding process material by students. Research objectives This is for know perception student to use of educational games as a learning medium. Research This use quantitative descriptive. Data collected with distribution questionnaire to student class X, XI, XI and interview to class guardian MA Tuhfatul Ulum. Validity test results in questionnaire declared valid, whereas reliability test results Cronbach alpha value obtained the result is 0.731 above 0.7 minimum criteria indicating instrument reliable. Questionnaire results show percentage overall 83% with very good category, which shows height level acceptance, interest, and response positive student to application of educational games in the learning process. Findings This signify that educational game capable increase interest, motivation, activity, and creating atmosphere learn more​ pleasant.